PERSEPSI PENGGUNA TERHADAP LAYANAN PERPUSTAKAAN IPB - Abidin, Abidin; Eriyadi, Pebri (Perpustakaan Nasional RI, 2024)
Whether each organization is good or not depends on its service. In carrying out management and service activities, libraries and librarians must continue to improve the type and quality of their services. The Ministry of State Apparatus Empowerment and Bureaucratic Reform introduced new types of library services contained in the Minister of State Apparatus and Bureaucratic Reform Regulation Number 55 of 2022, including: research consultation services, collaborative research services, information literacy services and scientific field mapping services. Utilization of library services influences user perceptions of library services. This research uses descriptive qualitative methods. A descriptive qualitative format is used to interpret library services to library users. Research data collection was carried out by means of observation and interviews. Sample selection used purposive sampling technique and determination of sample size used snowball sampling technique. The results of this research describe user perceptions of new library services at the IPB Library. As many as 78% of informants were not aware of the new library services. All informants said they really needed the new library services. There needs to be commitment from the institution and readiness of librarians to support service activities in the library.